2011
DOI: 10.1038/mt.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-penetrating Peptide Suppresses Inflammation by Inhibiting NF-κB Signaling

Abstract: Nuclear factor-κB (NF-κB) is a central regulator of immune response and a potential target for developing anti-inflammatory agents. Mechanistic studies suggest that compounds that directly inhibit NF-κB DNA binding may block inflammation and the associated tissue damage. Thus, we attempted to discover peptides that could interfere with NF-κB signaling based on a highly conserved DNA-binding domain found in all NF-κB members. One such small peptide, designated as anti-inflammatory peptide-6 (AIP6), was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…NF-κB is a central regulator of the immune response and is a potential target for the development of anti-inflammatory agents. For example, anti-inflammatory peptide-6 (AIP6) suppressed inflammation by inhibiting NF-κB signaling in mice [29]. Accordingly, we also found that C-BF also suppressed LPS-inducing inflammation by inhibiting the IκB-α-NF-κB signaling pathway in porcine macrophages in vitro.…”
Section: Discussionmentioning
confidence: 82%
“…NF-κB is a central regulator of the immune response and is a potential target for the development of anti-inflammatory agents. For example, anti-inflammatory peptide-6 (AIP6) suppressed inflammation by inhibiting NF-κB signaling in mice [29]. Accordingly, we also found that C-BF also suppressed LPS-inducing inflammation by inhibiting the IκB-α-NF-κB signaling pathway in porcine macrophages in vitro.…”
Section: Discussionmentioning
confidence: 82%
“…Cell proliferation was assessed by cell counting and [3H]-thymidine incorporation assay. Apoptosis was analyzed by flow cytometry as previously described (Wang et al, 2011). Details are found in Supplementary Materials and Methods online.…”
Section: Cell Proliferation and Apoptosis Assaysmentioning
confidence: 99%
“…Most CPPs, such as TAT [14], penetratin [15] and polyarginines [16], have a net positive charge. Although the minimum positive net charge of polyargineines for efficient cell penetration is +8 [12,16], the shortest CPP is CPP5(RKRWR) [21]. Amphipathic CPPs such as pVEC [17], transportan [13], MPG [18] and Pep-1 [19] have both cationic and hydrophobic amino acids.…”
Section: Introductionmentioning
confidence: 99%